Thermal-mechanical coupling simulation and experimental research on the grinding of zirconia ceramics. (November 2019) - Wan, Linlin; Li, Le; Deng, Zehui; Deng, Zhaohui; Liu, Wei
Abstract: A thermal-mechanical (TM) coupling simulation model of zirconia (ZrO2 ) grinding was created based on the finite element method to simulate the subsurface damage (SSD), the workpiece stress and the grinding temperature. A series of orthogonal experiments were accomplished by using an MGK7120 × 6/F NC surface grinder. The results show good agreement between the experiment and simulation. With the rotation of the grinding wheel, the abrasive grains gradually cut into the workpiece, and the workpiece stress increases with the contact time between the abrasive grains and the workpiece. When the abrasive grain just completely cuts into the workpiece, the grinding temperature reaches its maximum. The proposed simulation model for TM coupling exhibits a higher accuracy than that of the pure mechanics simulation model, with an absolute deviation of less than 6% for the simulation of SSD depth. During the grinding process, the effect of the grinding depth ( a p ) on the SSD depth is the greatest, followed by the effect of wheel speed ( v s ), and that of workpiece speed ( v w ) is the least. Additionally, v s is negatively correlated with the SSD depth, while v w and a p are positively correlated with the SSD depth.